Some results in a new power graphs in finite groups - Jafari S.H. (Utilitas Mathematica, 2017)
The power graph of a group is the graph whose vertex set is the set of non-Trivial elements of group, two elements being adjacent if one is a power of the other. We define a new power graph and study on connectivity, diameter and clique number of this graphs. © 2015 Utilitas Mathematics.